Massive Pleural Effusion Leads to the Revelation of Malignant Pleural Mesothelioma: A Case Report - Wijaya, Gede Adi Prasetya; Oei, Ivan Leonard Winardy; Putra, Wayan Wahyu Semara; Novitasari, Novitasari (Jurnal Respirasi, 2026)
Introduction: Malignant mesothelioma is a cancer that develops from the thin layer of tissue covering visceral organs (mesothelium). Up to 80% of malignant mesothelioma cases are caused by asbestos exposure. This case report describes a 56-year-old female with massive left pleural effusion caused by malignant mesothelioma. Case: A 56-year-old female presented with complaints of shortness of breath for two months, accompanied by right chest pain. Her prior hospital history showed massive left pleural effusion and a prominent lesion in the parietal pleura, suspected as mesothelioma. She had undergone an indwelling pleural catheter insertion and a bronchoscopy examination. However, her complaints persisted. Physical examination revealed thoracic asymmetry and retraction of the left chest wall. Supporting imaging studies revealed a massive left pleural effusion with multiple prominent lesions in the parietal pleura. Conclusion: Asbestos exposure is a major cause of malignant mesothelioma. In this case, the patient had a history of asbestos exposure while working as a laborer in a building materials store, which led to the development of malignant mesothelioma, which caused a massive left pleural effusion. Since malignant mesothelioma is a rare and incurable disease with a generally poor prognosis, the patient’s management primarily involved supportive and palliative therapy to reduce symptoms.